Total syntheses of shizukaols A and E - Wu, Jian-Li; Lu, Yin-Suo; Tang, Bencan; Peng, Xiao-Shui (Springer Nature Publishing, 2018)
Shizukaols possess a common heptacyclic framework containing more than ten contiguousstereocenters and potential biological activities. Here we report that the total syntheses ofshizukaols A (1)and E(2), two lindenane-type dimers from the Chloranthaceae family, areachieved via a modified biomimetic Diels–Alder reaction. The common crucial biomimetic diene23and ethylene species (6,17) are obtained through either a highlyZ-selective olefination ofα-siloxy ketone with ynolate anions or an intramolecular Horner–Wadsworth–Emmons olefinationfrom commercially available Wieland–Miescher ketone (7). This synthetic approach here opensup practical avenues for the total syntheses of the intriguing Chloranthaceae family members, aswell as the understanding of their relevant biological action in nature